Mastering structural heart disease - De Marchena, Eduardo; Gomez, Camilo A. (Camilo Andres), 1984- (Hoboken, NJ : Wiley, 2023)
"The aim of this book is to incorporate the different structural cardiology areas, latest techniques, devices, clinical research trials, future directions and innovation ideas into a practical and friendly "questions and answers" format, augmented by cases and reviews. The most renowned worldwide specialists on each of the topics will provide a concise overview, with valuable insights, knowledge and practical tips based on their experience. This will be supplemented by online clinical cases and vignettes for a complete overview of the topics in an absorbing, simplified method. The aim of this book is to be a valuable educational resource for interventional cardiologists, general cardiologists, cardiac surgeons, fellows in training and internists"--
Keywords: Heart -- Diseases -- Treatment; Heart Diseases -- therapy; Heart Diseases -- physiopathology; Electronic books